Penggunaan Harta Bersama Sebagai Marhun Dalam Pembiayaan di PT.PNM ULAMM Syariah Cabang Gunung tua Perspektif Fatwa Nomor 92/DSN-MUI/IV/2014 - Rizkiany Siregar; Cahaya Permata (Mahesa Research Center, 2023)
Marhun, used as collateral in financing transactions, is an asset that must be fully owned by the lender (rahin) in accordance with Sharia principles. However, in reality, there is a practice at PT. PNM ULAMM Sharia Branch Gunung Tua where financing transactions using the rahn system involve marhun that constitutes shared ownership. This research aims to identify the factors driving lenders to utilize jointly owned assets as marhun, the resulting legal consequences of this practice, and to analyze the practice based on the Fatwa DSN MUI No. 92/DSN-MUI/IV/2014. The methodology employed in this research is an empirical juridical approach utilizing both conceptual approaches and real-life case studies (living case studies). This research is descriptive-analytical in nature and involves data collection through interviews and document analysis. The research findings indicate that the utilization of jointly owned assets as marhun in rahn financing arises from the inadequate understanding of customers regarding the Sharia principles governing rahn financing.